Clinical Sports Nutrition - Edited By Burke, Louise, 1959 and Deakin, Vicki (Sydney McGraw-Hill, 2007)
A comprehensive reference that provides sports nutrition information, coupled with advice on how to apply sports nutrition guidelines in a clinical and practical framework. This book covers a range of topical issues on sports nutrition, presenting the theory and research findings
Include Index and Illustrations
Keywords: Athletes--Nutrition -- Physical fitness--Nutritional aspects -- Sports--Physiological aspects